Modified Dual Hepatic Vein Anastomosis in Pediatric Living-Donor Liver Transplantation Using Left Lateral Segment Grafts With Two Wide Orifices - Hou, Yuchen; Wan, Ping; Feng, Mingxuan; Qiu, Bijun; Zhou, Tao; Zhu, Jianjun; Luo, Yi; Zhang, Jianjun; Xia, Qiang (Frontiers in Pediatrics, 2021)
Background: The anatomic variation of hepatic vein in the left lateral segment (LLS) increases the risk of outflow complication in pediatric living liver transplantation (LDLT). Here, we share a modified method for dual hepatic vein reconstruction in pediatric LDLT using LLS with two wide orifices. Methods: From Sep 2018 to Dec 2019, 434 pediatric LDLTs using LLS were performed in our center. Hepatic veins of grafts were classified into three types with emphasis on the number, size, and location of orifices at the cut surface: a single opening (type I, n = 341, 78.57%); two adjacent orifices (type II, n = 66, 15.21%); two wide orifices with orifices distances <20 mm (type IIIa, n = 15, 3.46%); and two wide orifices with orifices distances >20 mm (type IIIb, n = 12, 2.76%). Rv was defined as the ratio of diameter of V2 and V3 (refer to hepatic vein drained segments II and III). We developed a modified dual hepatic vein anastomosis to reconstruct outflow for type IIIb grafts with Rv ≤1. Briefly, the hepatic vein of segment II was anastomosed to the common stump of middle hepatic vein (MHV) and left hepatic vein (LHV), followed by unification of V3 and the longitudinal incision orifice in inferior venous cave (IVC). Results: During median follow-up of 15.6 months (7.5–22.9 months), no hepatic vein complications occurred. Conclusion: This novel modified dual hepatic vein anastomosis could serve as a feasible surgical option for type IIIb LLS grafts with Rv ≤1 in pediatric LDLT.